Explorers and Expeditions, Arctic - Mikkelsen, Ejnar, 1880-1971; American Geographical Society of New York (1906)
Correspondence between Ejnar Mikkelsen and the American Geographical Society, as well as other individuals, regarding the proposed expedition to the Beaufort Sea.